ANALISIS KINERJA SAHAM-SAHAM INDIVIDUAL PERUSAHAANBUMN DI BURSA EFEK INDONESIAPERIODE JANUARI–DESEMBER 2010 - Chairani . (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
The purpose of this study was to explain the individual stock returns, systematic risk of the stock, stock performance and stock performance ratings of BUMN’s stock that start from Januari to Desember 2010. The Stocks performance were analyzed by calculating stock performance that using Jensen approach (αJ), rank the result, starting from the largest positive value to the smallest. The highest return of the stock was 0,2248 and the higest systematic risk was 114,618, ie., PT Semen Gresik Persero stocks, the best performance of the stock was 0,0361, i.e., PT Bank Negara Indonesia Persero stocks, and the worst performance was -0,1015 i.e., PT Semen Gersik Persero stock. This research result can be used as an investor consideration in assessing the performance of the company stock incorporated in BUMN that can provide the benefit as expected and indicate low systematic risk.Keywords: Stock Return, systematic risk of the stock, stock performance, Jensen Index(αJ),BUMN